Consumer Interpretation of the Term Plant-Based Diet - Shannon Menhardt; Anna Herby; Neal Barnard; Emily Forbes (American Journal of Lifestyle Medicine, 2026)
The objective of this study was to examine how the public interprets the term “plant-based.” A self-administered survey was conducted July 7-9, 2025, following the Best Practices for Survey Reach of the American Association of Public Opinion research. A total of 2202 participants responded. Participants were asked their understanding of the term “plant-based.” Population data were weighted to approximate a target sample of adults based on education, age, race, and region. Descriptive statistics were reported using chi-squared test. Fifty-six percent equated “plant-based” to vegan, 35% with eating abundant plant foods as part of an omnivorous diet, 2% chose “other” and 7% chose “don’t know.” Those aged 65-94 were more likely to equate the term with vegan (63%), while those aged 18-34 (51%), Hispanics (48%), Asian Americans (46%), and adults from northeastern United States (48%) were least likely. Use of “plant-based” without definition leaves room for misinterpretation.